2003
DOI: 10.1097/00004872-200311000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The G???217A variant of the angiotensinogen gene affects basal transcription and is associated with hypertension in a Taiwanese population

Abstract: Our study showed a significant association between the -217A variant of the AGT gene and hypertension. This variant plays a functional role in basal transcription of AGT, and may confer a risk for hypertension in Taiwanese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
6
11
0
Order By: Relevance
“…As an association has been identified between the common variant of M235 T in the AGT gene and EH occurrence, 2 several studies were performed in an effort to identify other genetic polymorphisms which may influence BP. [13][14][15][16] A community-based study showed that the T174 M and M235 T polymorphisms were associated with the onset of EH in Japanese, especially in those consuming high-salt diet, 15 and this was consistent with the findings from our current study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As an association has been identified between the common variant of M235 T in the AGT gene and EH occurrence, 2 several studies were performed in an effort to identify other genetic polymorphisms which may influence BP. [13][14][15][16] A community-based study showed that the T174 M and M235 T polymorphisms were associated with the onset of EH in Japanese, especially in those consuming high-salt diet, 15 and this was consistent with the findings from our current study.…”
Section: Discussionsupporting
confidence: 92%
“…9,10,13,14 Several functional studies have indicated that AGT A-6G, A-20C and G-217A polymorphisms in the promoter region play important roles in regulating the AGT gene transcription and expression. [17][18][19] In a recent study, Dickson et al 10 further testified the hypothesis that the polymorphisms in the AGT promoter may affect cell function, specifically regulation in the level of AGT transcription in AGT-producing tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our result on significant association of AA genotype (tested under the recessive model) and allele A at -217 with EHT is in accordance with the reports of Wu et al, 50,67 while it is in contrast to the finding of Jain et al, 49 who reported a significant association of AA genotype and allele A with hypertension in the dominant model.…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of our results from a transcriptional activity study of the AGT gene, we found that a more upstream promoter region, in addition to the core-promoter element 1 that contains the A-20C and G-6A polymorphisms, 21 also plays a critical role in transcriptional control. 22 Therefore, we also chose the G-152A and G-217A polymorphisms in this upstream region for the present study.…”
mentioning
confidence: 99%